AKAP79 Selectively Enhances Protein Kinase C Regulation of GluR1 at a Ca(2+)-Calmodulin-dependent Protein Kinase II/Protein Kinase C Site - Tavalin, Steven J. (American Society for Biochemistry and Molecular Biology, 2008)
Enhancement of AMPA receptor activity in response to synaptic plasticity inducing stimuli may arise, in part, through phosphorylation of the GluR1 AMPA receptor subunit at Ser-831. This site is a substrate for both Ca(2+)-calmodulin-dependent protein kinase II (CaMKII) and protein kinase C (PKC). However, neuronal protein levels of CaMKII may exceed those of PKC by an order of magnitude. Thus, it is unclear how PKC could effectively regulate this common target site. The multivalent neuronal scaffold A-kinase-anchoring protein 79 (AKAP79) is known to bind PKC and is linked to GluR1 by synapse-associated protein 97 (SAP97). Here, biochemical studies demonstrate that AKAP79 localizes PKC activity near the receptor, thus accelerating Ser-831 phosphorylation. Complementary electrophysiological studies indicate that AKAP79 selectively shifts the dose-dependence for PKC modulation of GluR1 receptor currents ∼20-fold, such that low concentrations of PKC are as effective as much higher CaMKII concentrations. By boosting PKC activity near a target substrate, AKAP79 provides a mechanism to overcome limitations in kinase abundance thereby ensuring faithful signal propagation and efficient modification of AMPA receptor-mediated responses.